METHODS OF LEARNING LISTENING COMPREHENSION - Qilicheva, Gulrukh (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to address methodological challenges in foreign language education by focusing on oral comprehension and listening strategies as critical components of second language acquisition. Method: Employing a qualitative review, the research analyzes current teaching methods and classroom listening practices through a comparative lens to identify effective pedagogical approaches. Results: The findings reveal that structured listening activities, when coupled with explicit strategy training, enhance learner engagement and improve comprehension accuracy. Students exposed to focused techniques such as attention management, content prediction, and auditory interpretation consistently demonstrated better understanding across diverse spoken contexts. Novelty: The study contributes to the field by bridging the gap between theoretical acknowledgment of listening skills and their practical implementation in language instruction. It emphasizes the integration of listening strategies into mainstream curriculum design rather than treating them as supplementary skills, highlighting the necessity for teacher training and curriculum adaptation. This approach provides learners with applicable tools to navigate authentic spoken communication, marking a shift toward more effective and learner-centered listening instruction.